Issues in islamic education in early marriage families in kundisari village - Mohammed Hafiz Ali Wafa; Rifatu Ayun; Husna Nashihin; Anwar Ma'rufi (Amorti: Jurnal Studi Islam Interdisipliner, 2024)
This research is based on data from the Ministry of Women's Empowerment and Protection of the Republic of Indonesia in 2022 which indicates that there are around 52,000 marriage dispensation cases that will go to the religious courts. Around 34,000 of these cases were triggered by the faktor of love which prompted parents to apply for their children to be married off immediately. Various faktors causing early marriage include pregnancies outside of marriage, environmental influences, and family faktors such as economic limitations. Individual faktors such as physical development and the influence of social media also play a role in this problem. The purpose of this study was to identify the causal faktors and solutions to the problems of Islamic education in families of early marriage in Kundisari Kedu Village, Temanggung. The method used is a qualitative approach with descriptive methods, with data collection techniques including observation, documentation, and interviews with residents of Kundisari village. The results of the study show that the lack of parental education and limited knowledge of Islamic education affect children's education. Busy parents, lack of consistent application of religious teachings, and lack of provision for parents are also problems in Islamic education in early marriage families. Therefore, solutions can be found through an Islamic family environment, increased parental education, open communication, and monitoring the use of technology.